PRINSIP KERJASAMA DALAM INTERAKSI ANTARA SISWA DENGAN GURU DI SMP NEGERI 2 KRIAN: PRINSIP KERJASAMA DALAM INTERAKSI ANTARA SISWA DENGAN GURU DI SMP NEGERI 2 KRIAN - Kartika Wahyuningsih; Luluk Isani Kulup (Universitas PGRI Adi Buana Surabaya, 2015)
Politeness is ethics in public communication, of course, having regard to the choice of words is good and right and need to know with whom and where to communicate. The researchers used a qualitative approach because this research itself aims to menjelasan and describe the use of the principle of cooperation that appear in the interaction between students and teachers in Junior High School 2 Krian. The primary data obtained directly through field surveys using all the original data collection methods. Secondary data were obtained from the data collection agencies that publish the data to the user community. This research data is speech or units of conversation between students and teachers in the Junior High School 2 Krian. Sources of data in the study is the subject of where the data can be obtained (Arikunto, 2010: 172). Source of data that students and teachers of SMP Negeri 2 Krian. Based on the findings of the data analysis of the data and found some maxims of cooperation in the interaction between students and teachers in Junior High School 2 Krian. Maksim this cooperation is based on the opinion of Grice consisting of four maxims. The maxim is a maxim (1) Quantity; (2) Quality; (3) Relevance; (4) ways or execution.